2022
DOI: 10.52547/rbmb.10.4.573
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Oncogenic Human Papillomavirus in Cervical Cancer Patients in Riau Province Indonesia

Abstract: Background: Cervical cancer is the fourth most deadly cancer in the world, and it is caused by infection of high-risk subtypes of Human PapillomaVirus (HPV) in most cases. The aims of this study were to determine the prevalence oncogenic HPV in cervical cancer patients in Riau Province Indonesia and to determine the clinical manifestation of HPV in cervical cancer patients in Riau Province Indonesia. Methods: This research was a descriptive study conducted at Arifin Achmad General Hospital Riau from February t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Between 2015 and 2017, individual data from a countrywide cervical cancer screening program in rural China were collected. The researchers looked at 1,160,981 women aged 35 to 64 who received either cytology alone or high-risk HPV testing plus cytology or genotyping triage (Savira et al, 2022). Regardless of age, income, or country of residence, women found HPV self-sampling to be extremely acceptable.…”
Section: Literature Surveymentioning
confidence: 99%
“…Between 2015 and 2017, individual data from a countrywide cervical cancer screening program in rural China were collected. The researchers looked at 1,160,981 women aged 35 to 64 who received either cytology alone or high-risk HPV testing plus cytology or genotyping triage (Savira et al, 2022). Regardless of age, income, or country of residence, women found HPV self-sampling to be extremely acceptable.…”
Section: Literature Surveymentioning
confidence: 99%
“…Faktor predisposisi fluor albus pada wanita meliputi umur, status pernikahan, paritas, siklus menstruasi, metode kontrasepsi, riwayat gangguan reproduksi, tingkat pendidikan, dan pekerjaan (Imelda & Nurbaiti, 2018). Fluor albus merupakan gejala kedua terbanyak yang dialami oleh para wanita penderita kanker cervix setelah perdarahan pervaginam (Savira, et al, 2022). Sejauh ini, peneliti belum menemukan penelitian lain yang mengandung koneksi antara kejadian fluor albus dengan citra tubuh yang beredar secara daring.…”
Section: Pembahasanunclassified
“…Notably, there has been an increased upsurge in ADC incidence, which is more prevalent among young adult women (Fujiwara et al, 2014). The primary risk factor contributing to CC is the presence of oncogenic human papillomavirus (HPV) (Savira et al, 2022). Previous studies have revealed that HPV 16 and 18 types account for approximately 70% of HPV infections (Aalijahan and Ghorbian, 2019).…”
Section: Introductionmentioning
confidence: 99%